Kompetensi Pendidikan Agama dalam Surat Al-'Alaq Perspektif Tafsir Al-Misbah Karya Muhammad Quraish Shibah - Dewi Ayu; Taufik Abdillah Syukur (Hikmah: Journal of Islamic Studies, 2019)
The purpose of this study was to determine the Competence of Religious Educators based on Q.S. Al-‘Alaq's perspective on the Tafsir al-Misbah by M. Quraish Shihab. Research that uses the Pure library research method. The results of this study obtained data that the competence of religious educators in the Q.S. al-‘Alaq perspective of Tafsir Al-Misbah by M. Quraish Shihab consists of pedagogic competence, personality competence, social competence, and professional competence. This conclusion supports Article 10 of the Law of the Republic of Indonesia number 14 of 2005 concerning teacher competencies. Keywords: Competence, Religious Educator, Surat al-‘Alaq, Tafsir al-Misbah penelitian ini adalah untuk mengetahui Kompetensi Pendidik Agama berdasarkan Q.S. Al-Alaq perspektif tafsir al- Misbah karya M. Quraish Shihab. Penelitian yang menggunakan metode Pure library research. Hasil penelitian ini memperoleh data bahwa kompetensi pendidik agama dalam Q.S. al-‘Alaq perspektif tafsir al-Misbah karya M. Quraish Shihab terdiri dari kompetensi pedagogik, kompetensi kepribadian, kompetensi sosial, dan kompetensi profesional. Kesimpulan ini mendukung Pasal 10 Undang-Undang Republik Indonesia nomor 14 tahun 2005 tentang kompetensi guru. Kata Kunci: Kompetensi, Pendidik Agama, Surat al-‘Alaq, Tafsir al-Misbah